NATURE OF THE ADSORPTION OF THE NONIONIC SURFACTANT PENTAETHYLENE GLYCOL MONODODECYL ETHER ON A LUDOX SILICA SOL - Cummins, P; Penfold, J; Staples, E (1992)
Small-angle neutron scattering (SANS) has been used to characterize the nature of the adsorption of pentaethylene glycon monododecyl ether (C12EO5) on a ludox silica sol. The effects of pH and temperature on the adsorbed layer are described. The results are compared with those for hexaethylene glycol monododecyl ether (C12EO6), and some significant differences are observed. © 1992 American Chemical Society.